Pain Experience after Dental Implant Placement Compared to Tooth Extraction - Alaa W. AlQutub (International Journal of Dentistry)
Background. A patients’ main concern when visiting the dentist is the pain experience during the procedure and postoperatively. Patients who are undergoing dental surgical procedures in particular may experience more concerns and higher level of anxiety and stress that can affect their psychology and decision-making ability. A thorough discussion with the patients about the planned surgical procedure and the expected postsurgical pain and discomfort level is crucial to reduce their fear and stress. Despite increasing popularity of dental implants, limited data are available on pain experience related to surgical implant placement. This review is to discuss and compare postoperative pain and discomfort level after dental implant placement procedure and tooth extraction. The review has a clinical significance as it can be used as a reference when explaining to the patients about the anticipated pain and discomfort level after implant placement. Conclusion. Informing patients about implant placement surgical procedure and the anticipated postsurgical pain can reduce their anxiety level and affect postsurgical pain and discomfort. Implant placement surgical procedure is less unpleasant than tooth extraction, with less postsurgical pain and limitation of daily activities.